Detection of human papillomavirus genes in human oral tissue biopsies and cultures by polymerase chain reaction. - Maitland, N. J. (Nature Publishing Group, 1989)
We have used the polymerase chain reaction to detect DNA sequences related to human papillomavirus type 16, by simultaneous priming with oligonucleotides from the E6 and L1/L2 open reading frames of the HPV16 genome. The HPV16-related sequence is present at low levels in normal oral tissue, in addition to biopsies and cell cultures from patients with benign and malignant disease. Ultimate analysis of the amplified sequences from the E6(120bp) and L1/L2(173bp) regions of HPV16 was achieved by gel electrophoresis and comparative nucleotide sequencing. The oral carcinoma biopsies and tissue cultures contained DNA sequences which were identical to the E6 region of HPV16, but only rarely contained sequences closely related to the L1/L2 region. The PCR technology should permit the detection, identification and cloning of latent viruses from extremely small tissue biopsies. IMAGES: